2012
DOI: 10.1111/gcb.12079
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China

Abstract: Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long-term observation data of ChinaFLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity (GEP), ecosystem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
191
1
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 299 publications
(215 citation statements)
references
References 72 publications
19
191
1
4
Order By: Relevance
“…The highest carbon sink appeared in central subtropical forests (550±258 g C m -2 yr -1 ), and followed by warm temperate forests (492±37 g C m -2 yr -1 ) and northern subtropical forests (343 g C m -2 yr -1 ). Yu et al, 2013b;Chen et al, 2014;FLUXNET, 2013;Du et al, 2012;Wang et al, 2008;Liu et al, 2011aLiu et al, , 2011bDong et al, 2011aDong et al, , 2011bZhang et al, 2007 Grassland Yu et al, 2013b;Chen et al, 2014 Cool temperate forests showed lower carbon sink compared to warm temperate and temperate forests. Studies of specific ecosystem suggest that mature forests in Northeast, Southeast, and Southwest (Zhang et al, 2006a;Liu et al, 2014a;Tan et al, 2010Tan et al, , 2012Guan et al, 2006;Zhang et al, 2006b;Yan et al, 2012) and subtropical plantations (Liu et al, 2006;Wen et al, 2010) had strong carbon sequestration capacity.…”
Section: Evaluation Of Ecosystem Carbon Sink/source Based On Flux Meamentioning
confidence: 99%
See 3 more Smart Citations
“…The highest carbon sink appeared in central subtropical forests (550±258 g C m -2 yr -1 ), and followed by warm temperate forests (492±37 g C m -2 yr -1 ) and northern subtropical forests (343 g C m -2 yr -1 ). Yu et al, 2013b;Chen et al, 2014;FLUXNET, 2013;Du et al, 2012;Wang et al, 2008;Liu et al, 2011aLiu et al, , 2011bDong et al, 2011aDong et al, , 2011bZhang et al, 2007 Grassland Yu et al, 2013b;Chen et al, 2014 Cool temperate forests showed lower carbon sink compared to warm temperate and temperate forests. Studies of specific ecosystem suggest that mature forests in Northeast, Southeast, and Southwest (Zhang et al, 2006a;Liu et al, 2014a;Tan et al, 2010Tan et al, , 2012Guan et al, 2006;Zhang et al, 2006b;Yan et al, 2012) and subtropical plantations (Liu et al, 2006;Wen et al, 2010) had strong carbon sequestration capacity.…”
Section: Evaluation Of Ecosystem Carbon Sink/source Based On Flux Meamentioning
confidence: 99%
“…Temperate steppes and alpine meadows served as weak carbon sink (24±83, 45±59 g C m -2 yr -1 ). The grasslands in northern China probably served as a weak carbon source after disturbances, which differed substantially among ecosystems and years (Shi et al, 2006;Li et al, 2006;Fu et al, 2006Fu et al, , 2009Yu et al, 2013b).…”
Section: Evaluation Of Ecosystem Carbon Sink/source Based On Flux Meamentioning
confidence: 99%
See 2 more Smart Citations
“…Since its establishment, ChinaFLUX has developed rapidly and expanded from the initial eight sites into a national scale network, with observation sites covering most of the terrestrial ecosystem types in China (Fu et al, 2010). The network of flux towers in China provides extensive and reliable measurements of the CO 2 , H 2 O and energy fluxes with high temporal and spatial resolution, which enables the estimation and prediction of the respective spatiotemporal variability of the carbon and water cycles under the global climate change scenario (He et al, 2010;Fu et al, 2010;Yu et al, 2013;Wang et al, 2013). To correctly upscale these fluxes to regional and global level, the representativeness of the current network is an important aspect to consider (Sulkava et al, 2011).…”
Section: Introductionmentioning
confidence: 99%